2016
DOI: 10.1055/s-0036-1580709
|View full text |Cite
|
Sign up to set email alerts
|

Continued Compliance and Degree of Satisfaction in Nulligravida and Parous Women with Intrauterine Contraceptive Devices

Abstract: There was no difference in compliance or the degree of satisfaction or continued use of IUDs between nulligravida and parous women, suggesting that IUD use may be recommended for women who have never been pregnant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 34 publications
2
20
1
3
Order By: Relevance
“…Regarding the methods used previously by the IUD for reproductive planning, the combined oral contraceptive was the most reported use before the choice of the copper IUD. A similar data was found, from the 157 women who received the Device in a hospital in Recife, 113 previously used hormonal oral contraceptives, followed by injectables (63) and more than half reported that the choice for the Device occurred due to the desire to abandon the use of hormones (9) . It is believed that the choice for copper IUD can occur for several reasons, among them, the fact that there are no hormones, less chance of contraceptive failure due to the fact of not needing to remember about daily intake, durability of the action, among others.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Regarding the methods used previously by the IUD for reproductive planning, the combined oral contraceptive was the most reported use before the choice of the copper IUD. A similar data was found, from the 157 women who received the Device in a hospital in Recife, 113 previously used hormonal oral contraceptives, followed by injectables (63) and more than half reported that the choice for the Device occurred due to the desire to abandon the use of hormones (9) . It is believed that the choice for copper IUD can occur for several reasons, among them, the fact that there are no hormones, less chance of contraceptive failure due to the fact of not needing to remember about daily intake, durability of the action, among others.…”
Section: Discussionsupporting
confidence: 65%
“…Regarding the education of women in this study, most had completed high school, attention is drawn to the number of women with or attending higher education, being similar to the study conducted in Recife, Brazil, in which, among the women who received the IUD , nulliparous women on average had completed high school and those who had a previous delivery did not complete it (9) . What differs from the research carried out in a hospital in Pakistan, from the total of 1,230 women who received the copper IUD after delivery, 918 (73.4%) did not have high school (11) .…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…9,12,13 In this study, even greater satisfaction was observed when compared to the findings of a study conducted in the United States with more than 5,000 women, in which the satisfaction with IUD use was 80%, 9 and also with Australian women of various age groups. 14 The high rate of satisfaction with the use of pill and injectable methods is worthy of attention, since some studies show that these are precisely the contraceptives that women declare to be less satisfied with.…”
Section: Discussioncontrasting
confidence: 52%